EFEKTIVITAS KETERBUKAAN INFORMASI PUBLIK PADA BIRO HUMAS DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI SULAWESI TENGAH - Ekayatri, Ekayatri (Katalogis, 2020)
The purpose of this study was to find out the Implementation of Public Information Openness at the Public Relations Bureau and the Protocol of the Regional Secretariat of Central Sulawesi Province. The foundation of the theory used is the theory of Richard M. Steers (1985) which states that there are three factors in measuring the effectiveness of an organization, namely the achievement of goals, adaptation and integration. This type of research is Qualitative Descriptive which seeks to interpret and interpret the data that is pleasing to the facts, using purposive methods, data analysis and discussion with a qualitative analysis approach to collecting data and materials through observation and interviews with 6 informants. Based on the results of the discussion that the Effectiveness of Public Information Disclosure on the Public Relations Bureau and Protocol of the Central Sulawesi Provincial Secretariat has been running optimally in order to improve socialization activities at the District / City level regarding public information disclosure. However, the capacity of Human Resources still needs to be improved considering the use of technological developments in the Globalization Era which is increasingly sophisticated and efficient.